Análisis del comportamiento del consumidor de servicios de transporte provincial en la ciudad de Machala - Ortiz Romero, Jessica Katherine (2015)
Marketing today has become the quintessential assistant with commercial sciences to carry out their management in the field of sales and brand positioning or even retain the service in the consumer's mind, with this background we stand in the transport sector to analyze the problem in recent years has been taking this sector relative to consumers in the province of El Oro (Machala city) this service is requested daily and mobilizes a lot of money, are companies more to stimulate the economy, to enable a service on a rotating basis. This study was exploratory and descriptive, which took reference sample number whose reference is the INEC 2010 and has taken a sample of 400 people, this was only to establish tastes and preferences for a certain way a market focus goal a defined profile. According to the results it was established that what customers want is a good treatment at the transport unit and offices, plus comfort during travel it is very important to users, among these facilities, one for them is quite important, is access to internet wirelessly, and in turn access to cargo worth remembering that there are many purposes for which it is traveling, one of these may be issues of work, for which being connected is a necessity and if a transport unit provides the service, the customer will have preference for her over other cooperatives, the solution that arises is a plan marketing strategies, globally focused, and that every company must have and apply some point to increase sales.